OGLE-2014-BLG-1760: A Jupiter-Sun Analogue Residing in the Galactic Bulge - Rektsini NE; Ranc C; Koshimoto N; Beaulieu J-P; Bennett DP; Cole AA; Terry SK; Bhattacharya A; Bachelet É; Bond IA; Udalski A; Blackman JW; et al. (IOP Publishing on behalf of The American Astronomical Society, 2025)
We present the analysis of OGLE-2014-BLG-1760, a planetary system in the galactic bulge. We combine Keck Adaptive Optics follow-up observations in K-band with re-reduced light-curve data to confirm the source and lens star identifications and stellar types. The re-reduced Microlensing Observations in Astrophysics data set had an important impact on the light-curve model. We find the Einstein ring crossing time of the event to be ∼2.5 days shorter than previous fits, which increases the planetary mass-ratio and decreases the source angular size by a factor of 0.25. Our OSIRIS images obtained 6 yr after the peak of the event show a source-lens separation of 54.20 ± 0.23 mas, which leads to a relative proper motion of μrel = 9.14 ± 0.05 mas yr−1 and is larger than the previous light-curve-only models. Our analysis shows that the event consists of a Jupiter-mass planet of Mp = 0.931 ± 0.117 MJup orbiting a K-dwarf star of M* = 0.803 ± 0.097 M⊙ with a K-magnitude of KL = 18.30 ± 0.05, located in the galactic bulge or bar. We also attempt to constrain the source properties using the source angular size θ* and K-magnitude. Our results favor the scenario of the source being a younger star in the galactic disk, behind the galactic bulge, but future multicolor observations are needed to constrain the source and thus the lens properties.